Implementasi Kebijakan 1 Alamat Maksimal 3 Kartu Keluarga di Kecamatan Semampir Kota Surabaya - Rifki A.M, Muhammad; Agatha, Bidari Amelia; Oni, Tanti; Regar, Ely Kristin Br; Rani, Berliana Mustika (JOSH: Journal of Sharia, 2025)
This study looks at how Surabaya’s new policy limiting one house to a maximum of three family cards (Kartu Keluarga or KK) is being carried out in Kecamatan Semampir. The policy was introduced to fix inconsistencies in the population database, where many people were registered at addresses they no longer lived at—or never lived at to begin with. Some houses were found to have dozens of family cards linked to them, which created problems for service delivery and planning. Using a qualitative approach, this research draws on interviews, field observations, and official documents to understand how the policy is being implemented on the ground. While the city has started enforcing limits through a web-based system, the process hasn’t been smooth. In Semampir, the number of family cards flagged for removal is the highest in the city. Challenges include limited outreach, resistance from residents, and gaps in coordination across local government offices. The findings suggest that implementation depends not just on rules, but on how well they’re explained, how much support is available, and whether staff are equipped to follow through. This paper recommends improving communication with residents, strengthening interagency cooperation, and making sure local officials have the tools and training to manage changes in population data.